Role of Cyanobacteria in the assembly and dynamics of microbial communities on glacier surfaces - Yeteng Xu; Yang Liu; Tuo Chen; Shijin Wang; Guangxiu Liu; Gaosen Zhang; Wei Zhang; Minghui Wu; Ximing Chen; Binglin Zhang (iScience)
Summary: Glacier surface habitats are dynamic ecosystems that respond to local climatic and thermal changes, although the assembly mechanisms of microbial communities in these environments remain unclear. This study examined microbial communities on the surface of Baishui Glacier No. 1 across the accumulation, the intense melt, and the late melt periods. The absolute abundance of Cyanobacteria increased significantly, becoming the most abundant phylum by the end of the melt period. Cyanobacteria were strongly associated with other local microorganisms, especially in community structure, community assembly, and co-occurrence networks. The correlations between Cyanobacteria and other microorganisms shifted from predominantly mutualistic interactions, to being predominantly competitive interactions, and finally to mutualistic interactions with a portion of the community. Additionally, Cyanobacteria abundance positively correlated with nitrogen metabolism multifunctionality in other microorganisms, indicating a potential link between Cyanobacteria and nitrogen cycling. These findings provide new insights into microbial community dynamics and survival strategies on glacier surfaces.